2012
DOI: 10.4018/ijkbo.2012040101
|View full text |Cite
|
Sign up to set email alerts
|

Implications for Improving Accessibility to E-Commerce Websites in Developing Countries

Abstract: This research explores the accessibility issues with regard to the e-commerce websites in developing countries, through a subjective study of Sri Lankan hotel websites. A web survey and a web content analysis were conducted as the methods to elicit data on web accessibility. Factors preventing accessibility were hypothesized as an initial experiment. Hazardous design elements are identified through web content analysis, the results of which are utilized to develop specific implications for improving web access… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 29 publications
0
17
0
1
Order By: Relevance
“…The significance of web accessibility standards in e-commerce has been known around the world (Bernard and Makienko, 2011;Sohaib and Kang, 2012). Sambhanthan and Good (2012) believes that the lack of conformance to accessibility guidelines in e-commerce website reduce the overall accessibility and hence results in poor readability and less navigable page designs. The purpose of web accessibility is to help make the webpages operable for consumers of all ages and with disabilities such as colour blindness.…”
Section: Web Accessibility In B2c E-commercementioning
confidence: 99%
“…The significance of web accessibility standards in e-commerce has been known around the world (Bernard and Makienko, 2011;Sohaib and Kang, 2012). Sambhanthan and Good (2012) believes that the lack of conformance to accessibility guidelines in e-commerce website reduce the overall accessibility and hence results in poor readability and less navigable page designs. The purpose of web accessibility is to help make the webpages operable for consumers of all ages and with disabilities such as colour blindness.…”
Section: Web Accessibility In B2c E-commercementioning
confidence: 99%
“…In addition, according to Zuo, Zillante [14], in a study of 50 international contractors, they found that almost 80% of the companies revealed their sustainability policies through their websites. Moreover, websites are used to publicise information relating to organisational matters [15] and have been chosen as a data source by many researchers for measuring sustainability practices [16]; identifying corporate social responsibility among the top 10 universities [13]; exploring e-commerce in developing countries [17]; investigating market orientation in local government [18]; investigating hotel information quality [19]; investigating tourism [15,20,21]; and examining government sustainability policy [22]. Therefore, this study ascertains that web content analysis is a legitimate research tool.…”
Section: Methodsmentioning
confidence: 99%
“…Considerable research has been conducted on businesses' development and use of websites (Rotchanakitumnuai, Kaewkitipong, & Ractham, 2011) and on government websites (Bertot, Jaeger, & Grimes, 2010;Shareef, Kumar, Kumar, & Dwivedi, 2011;United Nations, 2008), but previous research on nonprofit websites is outdated in the fast-paced information and communications technology (ICT) field (Tuckman, Chatterjee, & Muha, 2004); has focused on adoption of websites (Clerkin & Gronbjerg, 2007;Manzo & Pitken, 2007); or has concentrated on particular segments of web technologies, such as social media (Nah & Saxton, 2012;Waters, Burnett, Lamm, & Lucas, 2009) and online fundraising (Goecks, Voida, Voida, & Mynatt, 2008). Very few studies, business or nonprofit, even focus on website evaluation in less developed nations (Hasan, Morris, & Probets, 2013;Sambhanthan & Good, 2013). Research on nonprofit websites in less developed areas often focuses on particular case studies, such as crowdsourcing (Gao, Barbier, & Goolsby, 2011).…”
Section: Introductionmentioning
confidence: 99%